Clinical observations on hospitalized patients with virologically confirmed dengue hemorrhagic fever In Jakarta, Indonesia 1975 - 1983 - Sumarmo Sumarmo; Suharyono Wuryadi; D. J. Gublew (Paediatrica Indonesiana, 1986)
From 1975 to 1983, we clinically studied 1,451 serologically confirmed cases of dengue hemorrhagic fever in Jakarta, Indonesia. Of these cases, 142 were virologically confirmed. Considering these 142 cases, dengue type 3 was the predominant virus type isolated, but all 4 dengue virus serotypes were found. Dengue type 3 was the serotype most frequently associated with severe infections. Whereas 67 (47%) of the 142 patients had a dengue type 3 infection, this serotype was associated with 27 of the 34 fatal cases (79%). Dengue type 3 was found in 42 of the 75 cases with shock (56%), 31 of the 42 cases with encephalopathy (74%), and 19 of the 30 cases with gastrointestinal bleeding (63%).